Flexible composite solid electrolyte film capable of being continuously produced and preparation method thereof
By adjusting the pore coverage, pore area and speed difference in the vacuum suction filter device, uniform dispersion of inorganic solid electrolyte in the porous base film is achieved, and the problems of mechanical strength and large-scale production of composite solid electrolyte films are solved, and a high-performance flexible composite solid electrolyte film is obtained.
Patent Information
- Application Number
- CN202510054163.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-14
AI Technical Summary
It is difficult for the prior art to achieve uniform dispersion of inorganic fillers in polymer matrix and high mechanical strength and large-scale continuous production of composite solid electrolyte films.
A vacuum suction filter device is used to regulate the pore coverage, pore area and the speed difference between the porous base film containing inorganic solid electrolytes, so as to achieve uniform dispersion of inorganic solid electrolytes, and a dense and complete continuous production flexible composite solid electrolyte film is prepared.
It realizes uniform dispersion of inorganic solid electrolytes in the porous base film, improves the mechanical strength and electrochemical performance of the film, and is suitable for the efficient energy storage and safety requirements of batteries.
Smart Images

Figure BDA0005240876060000151 
Figure HDA0005240876070000011 
Figure HDA0005240876070000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a flexible composite solid electrolyte film that can be produced continuously and a preparation method thereof. Background Art
[0002] With the increasing demand for energy and the improvement of environmental protection awareness, it is particularly important to develop new efficient and safe energy storage technologies. Although traditional liquid lithium-ion batteries are widely used in portable electronic devices and electric vehicles, they have limited energy density and safety hazards, such as flammability and leakage. Therefore, solid-state batteries, as a new type of energy storage technology, are widely regarded as an important development direction in the field of power batteries due to their high energy density, wide temperature range and superior safety.
[0003] The core component of solid-state batteries is the solid electrolyte, which can be divided into inorganic solid electrolytes, polymer electrolytes and composite solid electrolytes. Inorganic solid electrolytes are favored for their high ionic conductivity and wide electrochemical window, but their brittleness and poor contact with electrodes limit their application. Polymer electrolytes are known for their flexibility and good electrode contact, but their low ionic conductivity and poor mechanical and electrochemical stability are their disadvantages. Composite solid electrolytes combine the advantages of both and are considered to be the most promising electrolyte material for high-performance lithium batteries.
[0004] However, the uniform dispersion of inorganic fillers in the polymer matrix, the high mechanical strength of the composite solid electrolyte film, and large-scale production are the main challenges currently faced. Although the existing organic / inorganic composite solid electrolyte film preparation technologies, such as coating and scraping infusion methods, have achieved the preparation of composite solid electrolytes to a certain extent, the mechanical properties of the prepared films are poor, and the inorganic components are prone to uneven dispersion, resulting in agglomeration. In addition, although the electrospinning method can obtain flexible composite films, its pores are large, the density is low, and the cost is high, making it difficult to achieve large-scale production. The commercial diaphragm substrate is mainly a polyolefin diaphragm, which is coated with a ceramic coating to improve heat resistance, but the control of coating thickness and the stability of the coating are also technical difficulties. The shedding of the ceramic coating will lead to problems such as increased internal resistance of the battery and poor cycle performance.
[0005] Therefore, how to ensure the uniform dispersion of inorganic fillers in the polymer matrix and improve the preparation process to facilitate the large-scale continuous production of composite solid electrolyte films remains a huge challenge and requires our continuous research. Summary of the invention
[0006] The present invention aims at the problems in the prior art and discloses a flexible composite solid electrolyte film that can be produced continuously and a preparation method thereof. In the preparation method of the present invention, a vacuum filtration device is used and the pore coverage and pore area on the surface of the vacuum filtration device and the speed difference between the vacuum filtration device and the porous base membrane containing an inorganic solid electrolyte are regulated, which is conducive to achieving a fully and uniform dispersion of the inorganic solid electrolyte in the porous base membrane, and preparing a dense and complete flexible composite solid electrolyte film that can be produced continuously.
[0007] The present invention is achieved through the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a flexible composite solid electrolyte film that can be produced continuously; the preparation method comprises:
[0009] S1: Preliminary compounding of a mixed solution A containing an inorganic solid electrolyte and a porous base membrane in operation; the porous base membrane has a porosity of 50-90% and a thickness of no more than 200 microns;
[0010] S2: preparing a composite solid electrolyte film precursor by subjecting the porous base film containing the inorganic solid electrolyte after preliminary compounding to a vacuum filtration device;
[0011] S3: drying and heat treating the composite solid electrolyte film precursor described in S2 to obtain a flexible composite solid electrolyte film;
[0012] The vacuum filtration device and the porous base membrane containing inorganic solid electrolyte are both in operation, the speed difference between the two is 0.3-2.5 m / min, the filtration pressure between the porous base membrane containing inorganic solid electrolyte and the vacuum filtration device is 0.01-1 MPa; the pore coverage rate per unit area of the vacuum filtration device is 70-95%, and the pore area ranges from 0.01-10 mm 2 .
[0013] As a further solution, the particle size of the inorganic solid electrolyte is 1-500 nanometers; the solid content in the mixed solution A is in the range of 1-50 wt %; and the pore size of the porous base membrane in S1 is selected from 1-500 nanometers.
[0014] Furthermore, the particle size of the inorganic solid electrolyte is preferably 50-200 nanometers; the pore size of the porous base membrane in S1 is preferably 250-400 nanometers.
[0015] The present invention does not limit the type of inorganic solid electrolyte; researchers in this field can select a suitable type of inorganic solid electrolyte according to specific needs; as some examples: the type of inorganic solid electrolyte is selected from one or more of oxide solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, nitride solid electrolytes, phosphate solid electrolytes, and borate solid electrolytes; wherein the oxide solid electrolyte includes one or more of garnet-type solid electrolytes, perovskite-type solid electrolytes, or NASICON-type solid electrolytes. Garnet-type solid electrolytes include lithium lanthanum zirconium oxide (LLZO) or solid electrolytes obtained by element replacement, doping or modification of LLZO; perovskite-type solid electrolytes include lithium lanthanum titanium oxide (LLTO) or solid electrolytes obtained by element replacement, doping or modification of LLTO; NASICON-type solid electrolytes include lithium aluminum titanium phosphate (LATP) and lithium aluminum germanium phosphate (LAGP) or solid electrolytes obtained by element replacement, doping or modification of LATP or LAGP; sulfide solid electrolytes include LGPS or solid electrolytes obtained by element replacement, doping or modification of LGPS; halide solid electrolytes include Li2MnCl4 and Li2ZnCl4; nitride solid electrolytes include lithium nitride Li3N; phosphate solid electrolytes include lithium phosphate Li3PO4; borate solid electrolytes include LiBO2 and Li4B2O5.
[0016] The present invention does not limit the types of porous base membranes; researchers in the field can select appropriate types of porous base membranes according to specific needs; as some examples: the types of porous base membranes in S1 are selected from polymer-based porous base membranes or natural polymer-based porous base membranes; wherein the polymer-based porous base membranes include one or more of polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polyurethane (PU), polyacrylonitrile (PAN), polyethylene oxide (PEO), polystyrene (PS), polyvinyl chloride (PVC), polycarbonate (PC), polymethyl methacrylate (PMMA), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), copolymer of vinylidene fluoride and hexafluoropropylene (PVDF-HFP), and polyimide (PI). The natural polymer-based porous base membrane is selected from cellulose membranes and their derivatives.
[0017] As a further embodiment, the mixed solution A in S1 includes a solvent; the type of the solvent is selected from one or more of water, ethanol, isopropanol, glycerol, ethylene glycol, tetrahydrofuran, N,N-dimethylformamide, and N-methylpyrrolidine.
[0018] In principle, the present application does not limit the specific structural composition of the vacuum filtration device; technical personnel in this field can use equipment of different shapes and structures to perform vacuum filtration to prepare composite solid electrolyte film as needed; as a preferred specific implementation case: the vacuum filtration device in S2 is selected from a roller-shaped vacuum filtration device or a parallel box-type vacuum filtration device.
[0019] As a further solution, the roller-shaped vacuum filtration device includes a vacuum filtration roller for adsorbing a porous base membrane containing an inorganic solid electrolyte; the vacuum filtration roller is provided with a first rotating shaft to drive the roller to rotate; the vacuum filtration roller surface also has a first suction hole; used to realize the vacuum filtration function of the device on the porous base membrane containing an inorganic solid electrolyte. The vacuum filtration roller is driven to move by the rotation of the first rotating shaft, and then in the continuous production process, a suitable speed difference is generated with the moving porous base membrane containing an inorganic solid electrolyte, so as to promote the sufficient and uniform adsorption of the inorganic solid electrolyte in the porous base membrane.
[0020] As a further solution, the roller-shaped vacuum filtration device also includes a flexible covering film; the flexible covering film is adsorbed on the surface of the vacuum filtration roller through a second rotating shaft; it is used to cover the part of the vacuum filtration roller that does not contact the porous base membrane containing the inorganic solid electrolyte; it further improves the negative pressure retention rate of the roller-shaped vacuum filtration device, has a good vacuum adsorption effect on the porous base membrane containing the inorganic solid electrolyte, ensures that the inorganic solid electrolyte is fully, evenly and stably embedded in the porous base membrane, and prepares a flexible composite solid electrolyte film with better performance that can be continuously produced.
[0021] As a further solution, the parallel box-type vacuum filtration device includes a vacuum filtration box for adsorbing a porous base membrane containing an inorganic solid electrolyte; the surface of the vacuum filtration box has a second suction hole; used to realize the vacuum filtration function of the device on the porous base membrane containing an inorganic solid electrolyte; and a third rotating shaft is provided on each side of the vacuum filtration box to drive the movement of the porous base membrane containing an inorganic solid electrolyte.
[0022] The present invention does not specifically limit the manner in which the parallel box-type vacuum filtration device realizes movement, and researchers in this field may make a choice according to specific needs. As some specific examples: the present invention chooses to set a mobile platform at the bottom of the vacuum filtration box to realize the movement of the vacuum filtration device; and then realizes the preparation of a flexible composite solid electrolyte film during the production process.
[0023] In principle, the present invention does not specifically limit the specific shapes of the first air extraction hole and the second air extraction hole. Those skilled in the art can select air extraction holes of appropriate shapes according to their needs. As some specific examples: the first air extraction hole and the second air extraction hole can be selected from circular, square, elliptical, etc.
[0024] As a further solution, the operating speed of the vacuum filtration device is selected from 0.1-10 m / min, and the speed difference with the porous base membrane containing the inorganic solid electrolyte is preferably 0.5-2 m / min. The pore coverage per unit area of the vacuum filtration device is preferably 75-90%, and the pore area range is preferably 0.1-10 mm 2 .
[0025] As a further solution, the drying temperature in S3 is selected from 60-100 degrees, and the drying time is selected from 6-24 hours.
[0026] As a further solution, the heat treatment method in S3 is selected from hot pressing or roller pressing; the pressure range is 20-50kg / cm 2 , temperature is 50-130 degrees, time is 1-15min.
[0027] The present invention does not specifically limit the method for preliminary compounding of the mixed solution A in S1 and the porous base membrane. Those skilled in the art can select a suitable preliminary compounding method as needed; as an exemplary description, the method for preliminary compounding can be selected from one of a coating process and an immersion process.
[0028] In a second aspect, the present invention provides a flexible composite solid electrolyte film that can be produced continuously; the film is prepared by the preparation method of the first aspect; the film has a thickness of 10-40 μm and a tensile strength of 10-80 MPa.
[0029] In a third aspect, the present invention provides a battery or an energy storage device, wherein the battery or the energy storage device comprises the flexible composite solid electrolyte film described in the second aspect.
[0030] The characteristics and beneficial effects of the present invention are:
[0031] (1) The present invention adopts a vacuum filtration method to uniformly fill the inorganic solid electrolyte solution into the pores of the porous base membrane, and ensures the flatness of the porous base membrane by adjusting the pore coverage and pore area on the surface of the vacuum filtration device, which helps to achieve a good balance between the effective support and adsorption of the porous base membrane by the vacuum filtration device; and improves the uniform dispersion of the inorganic solid electrolyte in the porous base membrane.
[0032] (2) The present invention also regulates the speed difference between the vacuum filtration device and the porous base membrane. By regulating the appropriate speed difference, it helps to avoid the problem of poor vacuum filtration effect caused by the porous base membrane running too fast or too slow during production and preparation, and is more suitable for the industrial production of composite solid electrolyte membranes. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 It is a schematic diagram of a roller-shaped vacuum filtration device; Figure 1 (1) is a top view schematic diagram of the operation of a roller-shaped vacuum filtration device with a circular hole, Figure 1 (2) is a top view schematic diagram of the operation of a roller-shaped vacuum filtration device with square holes, Figure 1 (3) is a front view schematic diagram of the operation of the roller-shaped vacuum filtration device.
[0035] Figure 2 It is a schematic diagram of a parallel box type vacuum filtration device; Figure 2 (1) is a top view schematic diagram of the operation of a parallel box type vacuum filtration device with circular holes, Figure 2 (2) is a top view of a parallel box type vacuum filtration device with square holes. Figure 2 (3) is a front view schematic diagram of the operation of the parallel box type vacuum filtration device.
[0036] Reference numerals:
[0037] 1-vacuum filtration roller; 2-first rotating shaft; 3-first air suction hole; 4-flexible covering film; 5-vacuum filtration box; 6-second air suction hole; 7-third rotating shaft; 8-movable platform; 9-second rotating shaft. DETAILED DESCRIPTION
[0038] In order to facilitate the understanding of the present invention, the present invention will be described in more detail below, and embodiments of the present invention are given, but the scope of the present invention is not limited thereby.
[0039] In a first aspect, the present invention provides a method for preparing a flexible composite solid electrolyte film that can be produced continuously; the preparation method comprises:
[0040] S1: Preliminary compounding of a mixed solution A containing an inorganic solid electrolyte and a porous base membrane in operation; the porous base membrane has a porosity of 50-90% and a thickness of no more than 200 microns;
[0041] S2: preparing a composite solid electrolyte film precursor by subjecting the porous base film containing the inorganic solid electrolyte after preliminary compounding to a vacuum filtration device;
[0042] S3: drying and heat treating the composite solid electrolyte film precursor described in S2 to obtain a flexible composite solid electrolyte film;
[0043] The vacuum filtration device and the porous base membrane containing inorganic solid electrolyte are both in operation, the speed difference between the two is 0.3-2.5 m / min, the filtration pressure between the porous base membrane containing inorganic solid electrolyte and the vacuum filtration device is 0.01-1 MPa; the pore coverage rate per unit area of the vacuum filtration device is 70-95%, and the pore area ranges from 0.01-10 mm 2 .
[0044] In order to solve the problems that the inorganic solid electrolyte cannot be evenly distributed, the bonding force is not strong, and the coating layer is prone to falling off during the preparation process of the composite solid electrolyte film; as well as the shortcomings of the composite solid electrolyte film prepared in the prior art that is thick, has poor flexibility, and is not conducive to continuous production; the present application has conducted a new preparation process research, and chose to use vacuum filtration to evenly fill the prepared inorganic solid electrolyte solution into the pores of the porous base membrane; especially in the continuous production process, by controlling the pore distribution and size of the vacuum filtration device, the porous base membrane is used as a supporting skeleton to ensure that the porous base membrane containing the inorganic solid electrolyte is fully fitted with the vacuum filtration device; and the speed difference between the porous base membrane containing the inorganic solid electrolyte and the vacuum filtration device is regulated to ensure that the inorganic solid electrolyte can be fully filled into the porous base membrane under vacuum filtration, avoiding the generation of uneven dispersion of the inorganic solid electrolyte inside the porous base membrane, thereby ensuring that the porous base membrane has both flexibility and good mechanical strength. Finally, through dry heat treatment, the thickness of the flexible composite solid electrolyte film is further reduced, the contact between the inorganic solid electrolyte particles is made closer, and a continuous lithium ion transmission path is formed, thereby improving the ionic conductivity of the film and obtaining a dense, complete, and continuously producible flexible composite solid electrolyte film.
[0045] Compared with the prior art, the present invention adopts a simple preparation process by vacuum filtration, and in order to ensure that the inorganic solid electrolyte is fully and evenly dispersed in the porous basement membrane, the present application fully regulates the speed difference between the vacuum filtration device and the porous basement membrane containing the inorganic solid electrolyte during the production and preparation process, as well as the distribution of the pore area and pore coverage of the vacuum filtration device surface; specifically, we adjust the speed difference between the vacuum filtration device and the porous basement membrane containing the inorganic solid electrolyte, and further optimize the pore distribution and pore coverage of the surface of the vacuum filtration device. By accurately regulating the pore coverage and pore size per unit area of the vacuum filtration device, it is beneficial to maintain the flatness of the porous basement membrane containing the inorganic solid electrolyte during the vacuum filtration process, thereby achieving a good balance between the effective support and adsorption of the porous basement membrane; it is beneficial to improve the uniform dispersion of the inorganic solid electrolyte in the porous basement membrane.
[0046] At the same time, this application also finely regulates the speed difference between the vacuum filtration device and the porous base membrane containing inorganic solid electrolytes, aiming to avoid the poor vacuum filtration effect caused by the porous base membrane containing inorganic solid electrolytes moving too fast or too slow in the production and preparation process, and the uneven distribution of inorganic solid electrolytes caused by this. Through the optimization and adjustment of the above parameters, it can ensure that the inorganic solid electrolyte is evenly distributed in the porous base membrane, thereby improving the overall performance and stability of the solid electrolyte film; it is more suitable for the industrial production of composite solid electrolyte films.
[0047] As a further solution, the particle size of the inorganic solid electrolyte is 1-500 nanometers; the solid content in the mixed solution A is in the range of 1-50 wt %; and the pore size of the porous base membrane in S1 is selected from 1-500 nanometers.
[0048] The appropriate solid content range in the mixed solution helps to form a uniform dispersion effect when compounding with the porous base membrane, while avoiding the problem of porous base membrane clogging caused by excessive solid content. In addition, by precisely controlling the particle size of the inorganic solid electrolyte and the pore size of the porous base membrane, the distribution uniformity of the inorganic solid electrolyte in the porous base membrane can be effectively controlled during the production process, and the composite efficiency can be improved; thereby preparing a flexible composite solid electrolyte film with excellent electrochemical and mechanical properties.
[0049] Furthermore, the particle size of the inorganic solid electrolyte is preferably 50-200 nanometers; the pore size of the porous base membrane in S1 is preferably 250-400 nanometers.
[0050] The present invention does not limit the type of inorganic solid electrolyte; researchers in this field can select a suitable type of inorganic solid electrolyte according to specific needs; as some examples: the type of inorganic solid electrolyte is selected from one or more of oxide solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, nitride solid electrolytes, phosphate solid electrolytes, and borate solid electrolytes; wherein the oxide solid electrolyte includes one or more of garnet-type solid electrolytes, perovskite-type solid electrolytes, or NASICON-type solid electrolytes. Garnet-type solid electrolytes include lithium lanthanum zirconium oxide (LLZO) or solid electrolytes obtained by element replacement, doping or modification of LLZO; perovskite-type solid electrolytes include lithium lanthanum titanium oxide (LLTO) or solid electrolytes obtained by element replacement, doping or modification of LLTO; NASICON-type solid electrolytes include lithium aluminum titanium phosphate (LATP) and lithium aluminum germanium phosphate (LAGP) or solid electrolytes obtained by element replacement, doping or modification of LATP or LAGP; sulfide solid electrolytes include LGPS or solid electrolytes obtained by element replacement, doping or modification of LGPS; halide solid electrolytes include Li2MnCl4 and Li2ZnCl4; nitride solid electrolytes include lithium nitride Li3N; phosphate solid electrolytes include lithium phosphate Li3PO4; borate solid electrolytes include LiBO2 and Li4B2O5.
[0051] The present invention does not limit the types of porous base membranes; researchers in the field can select appropriate types of porous base membranes according to specific needs; as some examples: the types of porous base membranes in S1 are selected from polymer-based porous base membranes or natural polymer-based porous base membranes; wherein the polymer-based porous base membranes include one or more of polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polyurethane (PU), polyacrylonitrile (PAN), polyethylene oxide (PEO), polystyrene (PS), polyvinyl chloride (PVC), polycarbonate (PC), polymethyl methacrylate (PMMA), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), copolymer of vinylidene fluoride and hexafluoropropylene (PVDF-HFP), and polyimide (PI). The natural polymer-based porous base membrane is selected from cellulose membranes and their derivatives.
[0052] As a further embodiment, the mixed solution A in S1 includes a solvent; the type of the solvent is selected from one or more of water, ethanol, isopropanol, glycerol, ethylene glycol, tetrahydrofuran, N,N-dimethylformamide, and N-methylpyrrolidine.
[0053] In principle, the present application does not limit the specific structural composition of the vacuum filtration device; those skilled in the art can use equipment of different shapes and structures to perform vacuum filtration to prepare a composite solid electrolyte film as needed; as a preferred specific implementation case: the vacuum filtration device in S2 is selected from a roller-shaped vacuum filtration device or a parallel box-type vacuum filtration device. The vacuum filtration device and the porous base membrane can be controlled by independent mobile transmission devices to achieve speed difference movement.
[0054] The porous base film is a rollable film, and its movement can be controlled by a front and rear conveying device, which can be selected from conventional conveying devices such as rollers that move back and forth.
[0055] like Figure 1 As shown; as a further solution, the roller-shaped vacuum filtration device includes a vacuum filtration roller 1 for adsorbing a porous base membrane containing an inorganic solid electrolyte; the vacuum filtration roller 1 is provided with a first rotating shaft 2 to drive it to rotate; the surface of the vacuum filtration roller 1 also has a first suction hole 3; used to realize the vacuum filtration function of the device on the porous base membrane containing an inorganic solid electrolyte. The rotation of the first rotating shaft 2 drives the movement of the vacuum filtration roller 1, and then in the continuous production process, a suitable speed difference is generated with the moving porous base membrane containing an inorganic solid electrolyte, promoting the full and uniform adsorption of the inorganic solid electrolyte in the porous base membrane.
[0056] As a further solution, the roller-shaped vacuum filtration device also includes a flexible covering membrane 4; the flexible covering membrane 4 is adsorbed on the surface of the vacuum filtration roller 1 through the second rotating shaft 9; it is used to cover the part of the vacuum filtration roller 1 that does not contact the porous base membrane containing the inorganic solid electrolyte; it further improves the negative pressure retention rate of the roller-shaped vacuum filtration device, has a good vacuum adsorption effect on the porous base membrane containing the inorganic solid electrolyte, ensures that the inorganic solid electrolyte is fully, evenly and stably embedded in the porous base membrane, and prepares a flexible composite solid electrolyte film with better performance that can be continuously produced.
[0057] like Figure 2 As shown, as a further solution, the parallel box-type vacuum filtration device includes a vacuum filtration box 5 for adsorbing a porous base membrane containing an inorganic solid electrolyte; the surface of the vacuum filtration box 5 has a second suction hole 6; which is used to realize the vacuum filtration function of the device on the porous base membrane containing an inorganic solid electrolyte; and a third rotating shaft 7 is provided on both sides of the vacuum filtration box 5 to drive the movement of the porous base membrane containing an inorganic solid electrolyte.
[0058] The present invention does not specifically limit the manner in which the parallel box-type vacuum filtration device realizes movement, and researchers in the field may make a choice according to specific needs. As some specific examples: the present invention chooses to set a mobile platform 8 at the bottom of the vacuum filtration box 5 to realize the movement of the vacuum filtration device; and then realizes the preparation of a flexible composite solid electrolyte film during the production process.
[0059] In principle, the present invention does not impose any specific limitation on the specific shapes of the first air extraction hole 3 and the second air extraction hole 6. Those skilled in the art may select air extraction holes of appropriate shapes according to their needs. As some specific examples: the first air extraction hole 3 and the second air extraction hole 6 may be selected from circular, square, elliptical, etc.
[0060] As a further solution, the operating speed of the vacuum filtration device is selected from 0.1-10 m / min, and the speed difference with the porous base membrane containing the inorganic solid electrolyte is preferably 0.5-2 m / min. The pore coverage per unit area of the vacuum filtration device is preferably 75-90%, and the pore area range is preferably 0.1-10 mm 2 .
[0061] This application further regulates the speed difference between the vacuum filtration device and the porous base membrane containing inorganic solid electrolytes during the production and preparation process, as well as the distribution of the surface pore area and pore coverage of the vacuum filtration device. It is intended to achieve a good balance between the support and adsorption of the porous base membrane by regulating the pore coverage and pore area per unit area of the vacuum filtration device, thereby achieving tight adsorption on the basis of maintaining the structural integrity of the porous base membrane; promoting the full integration of the inorganic solid electrolyte inside the porous base membrane; at the same time, this application further regulates the speed difference between the vacuum filtration device and the porous base membrane containing inorganic solid electrolytes; the speed difference within the optimization range helps to achieve the best vacuum filtration effect in the continuous production process, ensuring the formation of a more dense flexible composite solid electrolyte film.
[0062] As a further solution, the drying temperature in S3 is selected from 60-100 degrees, and the drying time is selected from 6-24 hours.
[0063] As a further solution, the heat treatment method in S3 is selected from hot pressing or roller pressing; the pressure range is 20-50kg / cm 2 , temperature is 50-130 degrees, time is 1-15min.
[0064] Selecting the appropriate heat treatment pressure and temperature can help further reduce the thickness of the flexible composite solid electrolyte film, promote the close bonding between the inorganic solid electrolyte and the porous base membrane, and build a more continuous and uniform ion transmission path, thereby improving the ion conductivity during the battery charge and discharge cycle. In addition, it can further enhance the mechanical strength of the flexible composite solid electrolyte film to ensure its stability and reliability during battery assembly and use. Through further heat treatment and optimization of heat treatment conditions, the pores and defects after the inorganic solid electrolyte is filled in the film can also be effectively reduced, and a more stable interface between the inorganic solid electrolyte and the porous base membrane can be formed, which is crucial to improving the cycle life and safety of the battery.
[0065] The present invention does not specifically limit the method for preliminary compounding of the mixed solution A in S1 and the porous base membrane. Those skilled in the art can select a suitable preliminary compounding method as needed; as an exemplary description, the method for preliminary compounding can be selected from one of a coating process and an immersion process.
[0066] In a second aspect, the present invention provides a flexible composite solid electrolyte film that can be produced continuously; the film is prepared by the preparation method of the first aspect; the film has a thickness of 10-40 μm and a tensile strength of 10-80 MPa.
[0067] The flexible composite solid electrolyte film that can be continuously produced and obtained by the preparation process of the present invention has a lower thickness and better tensile strength; the composite mode in which the inorganic solid electrolyte is filled inside the porous base membrane is more stable, which helps to have good adaptability and cycle durability in the charge and discharge cycle of the battery; at the same time, the lower thickness helps to reduce the transmission resistance of ions, thereby improving the ion migration rate and the charge and discharge performance of the battery.
[0068] In a third aspect, the present invention provides a battery or an energy storage device, wherein the battery or the energy storage device comprises the flexible composite solid electrolyte film described in the second aspect.
[0069] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0070] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.
[0071] Example 1
[0072] The LATP inorganic solid electrolyte with a particle size of 50 nanometers is uniformly dispersed in NMP solvent to prepare a mixed solution A, wherein the solid content in the mixed solution A is 10wt%;
[0073] Polyethylene PE material is selected as the porous base membrane, with a porosity of 70%, a pore size of about 300 nanometers, and a thickness of 30 μm;
[0074] Preliminarily compounding the mixed solution A with the PE porous base film by coating;
[0075] The LATP particles are vacuum filtered into the pores of the PE porous base membrane by a parallel box-type vacuum filtration device to obtain a composite solid electrolyte film precursor; wherein, the running speed V1 of the inorganic solid electrolyte porous base membrane after the initial composite is 1m / min, the running speed V2 of the vacuum filtration box 5 is 1.5m / min, and the filtration pressure on the surface of the inorganic solid electrolyte porous base membrane and the vacuum filtration box 5 is 0.1MPa; the surface pore coverage rate of the parallel box-type vacuum filtration device is 80%, and the pore area is 2mm 2 .
[0076] The composite solid electrolyte film precursor was dried in an oven at 80°C for 12 h to remove the residual solvent in the film;
[0077] The dried film was heat-pressed at a pressure of 30 kg / cm 2 , temperature is 80 degrees, and holding time is 10 minutes; the obtained flexible composite solid electrolyte film has a thickness of 20μm and a tensile strength of 20MPa.
[0078] Example 2
[0079] The specific preparation method and steps are the same as those in Example 1, except that: the LATP particles are vacuum filtered into the pores of the PE porous base membrane by a roller-shaped vacuum filtration device to obtain a composite solid electrolyte film precursor; wherein, after the initial composite, the running speed V1 of the inorganic solid electrolyte porous base membrane is 1m / min, the running speed V2 of the vacuum filtration roller 1 is 1.5m / min, and the filtration pressure between the inorganic solid electrolyte porous base membrane and the vacuum filtration roller 1 is 0.1MPa. The surface pore coverage of the roller-shaped vacuum filtration device is 80% and the pore area is 2mm 2 .
[0080] Example 3
[0081] The specific preparation steps and methods are the same as those in Example 1, except that: the surface pore coverage of the parallel box-type vacuum filtration device is 85%, and the pore area is 1.5 mm 2 .
[0082] Example 4
[0083] The specific preparation steps and methods are the same as those in Example 2, except that: the surface pore coverage of the roller-shaped vacuum filtration device is 85% and the pore area is 3 mm 2 .
[0084] Example 5
[0085] The LLTO inorganic solid electrolyte with a particle size of 150 nanometers is uniformly dispersed in NMP solvent to prepare a mixed solution A, wherein the solid content in the mixed solution A is 5wt%;
[0086] Polyethylene PE material is selected as the porous base membrane, with a porosity of 80%, a pore size of about 300 nanometers, and a thickness of 30 μm;
[0087] Preliminarily compounding the mixed solution A with the PE porous base film by coating;
[0088] The LATP particles are vacuum filtered into the pores of the PE porous base membrane by a parallel box-type vacuum filtration device to obtain a composite solid electrolyte film precursor; wherein, the running speed V1 of the inorganic solid electrolyte porous base membrane after preliminary composite is 0.1m / min, the running speed V2 of the vacuum filtration box 5 is 0.6m / min, and the filtration pressure on the surface of the inorganic solid electrolyte porous base membrane and the vacuum filtration box 5 is 0.08MPa; the surface pore coverage rate of the parallel box-type vacuum filtration device is 80%, and the pore area is 2mm 2 .
[0089] The composite solid electrolyte film precursor was dried in an oven at 80°C for 12 h to remove the residual solvent in the film;
[0090] The dried film was heat-pressed at a pressure of 30 kg / cm 2 , temperature is 80 degrees, and holding time is 10 minutes; the obtained flexible composite solid electrolyte film has a thickness of 20μm and a tensile strength of 50MPa.
[0091] Example 6
[0092] The LLZO inorganic solid electrolyte with a particle size of 50 nanometers is uniformly dispersed in NMP solvent to prepare a mixed solution A, wherein the solid content in the mixed solution A is 20wt%;
[0093] Polyethylene PE material is selected as the porous base membrane, with a porosity of 80%, a pore size of about 300 nanometers, and a thickness of 80 μm;
[0094] Preliminarily compounding the mixed solution A with the PE porous base film by coating;
[0095] The LATP particles are vacuum filtered into the pores of the PE porous base membrane by a parallel box-type vacuum filtration device to obtain a composite solid electrolyte film precursor; wherein the running speed V1 of the inorganic solid electrolyte porous base membrane after preliminary composite is 8m / min, the running speed V2 of the vacuum filtration box 5 is 10m / min, and the filtration pressure on the surface of the inorganic solid electrolyte porous base membrane and the vacuum filtration box 5 is 1MPa; the surface pore coverage rate of the parallel box-type vacuum filtration device is 80%, and the pore area is 2mm 2 .
[0096] The composite solid electrolyte film precursor was dried in an oven at 80°C for 12 h to remove the residual solvent in the film;
[0097] The dried film was heat-pressed at a pressure of 30 kg / cm 2 , temperature is 80 degrees, and holding time is 10 minutes; the obtained flexible composite solid electrolyte film has a thickness of 40μm and a tensile strength of 80MPa.
[0098] Example 7
[0099] The LATP inorganic solid electrolyte with a particle size of 50 nanometers is uniformly dispersed in NMP solvent to prepare a mixed solution A, wherein the solid content in the mixed solution A is 25wt%;
[0100] Polypropylene PP material is selected as the porous base membrane, with a porosity of 60%, a pore size of about 300 nanometers, and a thickness of 30 μm;
[0101] Preliminarily compounding the mixed solution A with the PE porous base film by coating;
[0102] The LATP particles are vacuum filtered into the pores of the PE porous base membrane by a parallel box-type vacuum filtration device to obtain a composite solid electrolyte film precursor; wherein, the running speed V1 of the porous base membrane containing the inorganic solid electrolyte after the initial composite is 0.8m / min, the running speed V2 of the vacuum filtration box 5 is 1.5m / min, and the filtration pressure on the surface of the porous base membrane containing the inorganic solid electrolyte and the vacuum filtration box 5 is 0.08MPa; the surface pore coverage rate of the parallel box-type vacuum filtration device is 80%, and the pore area is 2mm 2 .
[0103] The composite solid electrolyte film precursor was dried in an oven at 80°C for 12 h to remove the residual solvent in the film;
[0104] The dried film was heat-pressed at a pressure of 40 kg / cm 2 , temperature is 80 degrees, and holding time is 10 minutes; the obtained flexible composite solid electrolyte film has a thickness of 15μm and a tensile strength of 15MPa.
[0105] Example 8
[0106] The LATP inorganic solid electrolyte with a particle size of 50 nanometers is uniformly dispersed in NMP solvent to prepare a mixed solution A, wherein the solid content in the mixed solution A is 30wt%;
[0107] Polyethylene PE material is selected as the porous base membrane, with a porosity of 80%, a pore size of about 350 nanometers, and a thickness of 30 μm;
[0108] Preliminarily compounding the mixed solution A with the PE porous base film by coating;
[0109] The LATP particles are vacuum filtered into the pores of the PE porous base membrane by a parallel box-type vacuum filtration device to obtain a composite solid electrolyte film precursor; wherein, the running speed V1 of the inorganic solid electrolyte porous base membrane after the initial composite is 1m / min, the running speed V2 of the vacuum filtration box 5 is 1.5m / min, and the filtration pressure on the surface of the inorganic solid electrolyte porous base membrane and the vacuum filtration box 5 is 0.1MPa; the surface pore coverage rate of the parallel box-type vacuum filtration device is 80%, and the pore area is 2mm 2 .
[0110] The composite solid electrolyte film precursor was dried in an oven at 80°C for 12 h to remove the residual solvent in the film;
[0111] The dried film was heat-pressed at a pressure of 50 kg / cm 2 , temperature is 80 degrees, and holding time is 10 minutes; the obtained flexible composite solid electrolyte film has a thickness of 15 μm and a tensile strength of 10 MPa.
[0112] Comparative Example 1
[0113] The specific steps and preparation method are the same as those in Example 1, except that: the running speed V1 of the porous base membrane containing the inorganic solid electrolyte after the initial compounding is 10 m / min, and the running speed V2 of the vacuum filtration box 5 is 2 m / min.
[0114] Comparative Example 2
[0115] The specific steps and preparation method are the same as those in Example 1, except that: the surface pore coverage of the parallel box-type vacuum filtration device is 95%, and the pore area is 20mm 2 .
[0116] Comparative Example 3
[0117] The specific steps and preparation method are the same as those in Example 1, except that a polyethylene PE material is selected as the porous base membrane, and the porosity thereof is 70%, the pore size is about 100 nanometers, and the thickness is 300 μm.
[0118] Comparative Example 4
[0119] The specific steps and preparation method are the same as those in Example 1, except that: LATP inorganic solid electrolyte with a particle size of 50 nanometers is uniformly dispersed in NMP solvent to prepare mixed solution A, wherein the solid content in the mixed solution A is 60 wt%.
[0120] Comparative Example 5
[0121] The specific steps and preparation method are the same as those in Example 1, except that the filtration pressure between the porous base membrane containing the inorganic solid electrolyte and the vacuum filtration device is 5 MPa.
[0122] Comparative Example 6
[0123] The specific steps and preparation method are the same as those in Example 1, except that: the dried film is subjected to hot pressing at a pressure of 70 kg / cm 2 , temperature is 150 degrees, and holding time is 5 minutes; the obtained flexible composite solid electrolyte film has a thickness of 8μm and a tensile strength of 5MPa.
[0124] Specific test methods and conditions:
[0125] Ionic conductivity: EIS is tested using the AC impedance method with an amplitude of 10mV and a frequency of 0.1 to 700,0000Hz.
[0126] Cycle test: positive electrode is LiNi 0.8 Co 0.1 Mn 0.1 The (NCM811) positive electrode is prepared by mixing 84wt.% NCM811, 8wt.% conductive carbon black (SP) and 8wt.% polyvinylidene fluoride (PVDF), and the negative electrode uses a lithium metal negative electrode. In a glove box with an argon atmosphere, the positive electrode shell, 811 positive electrode sheet, and the composite diaphragm are placed in order, 60μL of lithium-ion secondary battery electrolyte is added to the diaphragm, and then lithium sheets, steel sheets, shrapnel and negative electrode shells are placed in order, packaged, and pressurized to 350MPa to obtain a button battery. The battery was subjected to a 1C rate charge and discharge test at 25±2℃ (room temperature), and the charge and discharge cut-off voltage was 3.0V-4.3V.
[0127] Table 1
[0128]
[0129] It can be seen from the data in Table 1 that the continuously produced composite solid electrolyte films prepared by the preparation process of Examples 1-8 using the preparation process of the present invention have better tensile strength, electrochemical performance and cycle stability than those of Comparative Examples 1-6; this indicates that the present invention utilizes vacuum filtration and regulates the process and material parameters such as the pore coverage, pore area, and speed of the inorganic solid electrolyte particles, the pores of the porous base membrane, and the vacuum filtration device, which helps to evenly disperse the inorganic solid electrolyte into the porous base membrane material; thus, it is suitable for obtaining a composite solid electrolyte film with both flexibility and mechanical strength in a continuous production process; and exhibits good battery charge and discharge performance and cycle stability during the battery charge and discharge process.
[0130] It can be seen from Example 1 and Comparative Example 1 that the tensile strength of the composite solid electrolyte membrane in Comparative Example 1 is relatively low, and the ionic conductivity and cycle performance of the battery during the charge and discharge cycle are relatively poor; we believe that this is due to the large difference in the operating rate between the porous basement membrane containing inorganic solid electrolyte and the vacuum filtration housing 5, which causes the porous basement membrane to be unable to fully and evenly embed the inorganic solid electrolyte particles into the porous basement membrane during the composite process, and the degree of vacuum filtration is insufficient, resulting in more residual inorganic solid electrolytes on the surface of the porous basement membrane, and the prepared composite electrolyte membrane layer is thicker, and is not conducive to forming a continuous and unobstructed ion transmission channel, thereby affecting the overall performance of the composite membrane. In Example 1, the uniform distribution of the inorganic solid electrolyte particles in the porous basement membrane is ensured by optimizing the operating rate difference within the range, thereby improving the electrochemical properties and mechanical strength of the composite membrane.
[0131] It can be seen from Example 1 and Comparative Example 2 that the vacuum filtration device used in the present invention has different effects on the preparation of porous base membrane composite inorganic solid electrolyte by selecting different suction hole areas; the surface pore area used by the vacuum filtration device in Comparative Example 2 is too large compared with the embodiment, which can easily cause the porous base membrane to collapse when the porous base membrane is subjected to suction filtration and adsorption, resulting in an uneven surface of the composite membrane, and the inorganic solid electrolyte particles cannot be evenly embedded in the porous base membrane, thereby affecting the electrochemical properties and mechanical strength of the composite membrane.
[0132] It can be seen from Example 1 and Comparative Example 3 that the selected porous base membrane is too thick, which is not conducive to the uniform dispersion of the inorganic solid electrolyte inside the porous base membrane, resulting in a decrease in the electrochemical properties and mechanical strength of the composite solid electrolyte membrane. In Comparative Example 3, the thickness of the porous base membrane is 300μm, which is much greater than the thickness of the base membrane used in Example 1. Because the base membrane is too thick, the diffusion and distribution of the inorganic solid electrolyte particles inside the base membrane become difficult, resulting in uneven distribution of the electrolyte inside the composite membrane. This unevenness not only reduces the ionic conductivity of the electrolyte, but also weakens the mechanical strength of the composite membrane, making it easy to generate stress concentration during the battery charge and discharge process, thereby affecting the cycle stability and overall performance of the battery. In contrast, the thinner porous base membrane used in Example 1 contributes to the uniform dispersion of the inorganic solid electrolyte particles, thereby improving the electrochemical properties and mechanical strength of the composite membrane.
[0133] It can be seen from Example 1 and Comparative Example 4 that the composite solid electrolyte prepared in Comparative Example 4 has lower ionic conductivity and poorer cycle performance than that in Example. This is because the solid content of the inorganic solid electrolyte in the mixed solution A is too high, which causes the inorganic solid electrolyte inside the composite membrane to be unevenly distributed when it is composited with the porous base membrane, and it is easy to form larger electrolyte particles during the drying process. These particles form defects in the composite membrane, destroy the pore structure of the porous base membrane, and affect the ion transmission efficiency. In addition, the mixed solution with a high solid content is easy to block the pores of the porous base membrane during the filtration process, further reducing the electrochemical performance and mechanical strength of the composite membrane, which is not conducive to having good cycle stability in the charge and discharge cycle of the battery.
[0134] It can be seen from Example 1 and Comparative Example 5 that in the process of using a vacuum filtration device to filter the porous basement membrane containing an inorganic solid electrolyte, the filtration pressure between the porous basement membrane containing an inorganic solid electrolyte and the vacuum filtration device is 5MPa, and the adsorption pressure range optimized relative to the embodiment is too large, which easily leads to structural damage of the porous basement membrane, affecting the mechanical strength and electrochemical properties of the composite membrane. When the filtration pressure is too large, the pore structure of the porous basement membrane may be deformed or destroyed, so that the inorganic solid electrolyte particles cannot be evenly embedded in the porous basement membrane, thereby forming defects in the composite membrane, affecting the transmission efficiency of ions. In addition, too high filtration pressure may also cause the pores of the porous basement membrane to be blocked, further reducing the electrochemical properties and mechanical strength of the composite membrane, which is not conducive to the cycle stability in the battery charge and discharge cycle.
[0135] It can be seen from Example 1 and Comparative Example 6 that when the dried composite solid electrolyte membrane is further hot-pressed, the hot-pressing pressure and hot-pressing temperature used in Comparative Example 6 are larger than those in the embodiment. Although the obtained composite solid electrolyte membrane layer is lower than that in the embodiment, its tensile strength, ionic conductivity, cycle stability and other performances are poor. This is because when the hot-pressing pressure and temperature are too high, the inorganic solid electrolyte particles inside the composite membrane may aggregate, resulting in uneven electrolyte distribution, and at the same time, excessive hot-pressing conditions may destroy the pore structure of the porous base membrane, affecting the continuity of the ion transmission channel. This uneven electrolyte distribution and the destruction of the pore structure not only reduce the electrochemical properties of the composite membrane, but also weaken its mechanical strength, thereby easily generating stress concentration during the battery charge and discharge process, affecting the cycle stability and overall performance of the battery. In contrast, the suitable hot-pressing pressure and temperature used in Example 1 help to further reduce the thickness of the membrane layer while maintaining the integrity of the internal structure of the composite membrane, promote the close combination between the inorganic solid electrolyte and the porous base membrane, and construct a more continuous and uniform ion transmission path, ensuring the uniform distribution of the electrolyte particles, thereby improving the electrochemical properties and mechanical strength of the composite membrane.
[0136] It can be seen from Examples 1 and 2 that the roller-shaped vacuum filtration device and the parallel box-type vacuum filtration device used in the present invention can effectively achieve uniform compounding of the porous basement membrane and the inorganic solid electrolyte. By optimizing the suction pore area and pore coverage of the filtration surface and the adsorption pressure of the porous basement membrane containing the inorganic solid electrolyte, the porous basement membrane containing the inorganic solid electrolyte can be fully adsorbed. In addition, by adjusting the speed difference between the roller-shaped vacuum filtration device and the parallel box-type vacuum filtration device and the porous basement membrane containing the inorganic solid electrolyte during production and use, the uniform distribution of the inorganic solid electrolyte particles in the porous basement membrane is ensured.
[0137] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a flexible composite solid electrolyte film that can be produced continuously; characterized in that: The preparation method comprises: S1: Preliminarily compounding a mixed solution A containing an inorganic solid electrolyte with a porous base membrane in operation; the porous base membrane has a porosity of 50-90% and a thickness of no more than 200 microns; S2: preparing a composite solid electrolyte film precursor by subjecting the porous base film containing the inorganic solid electrolyte after preliminary compounding to a vacuum filtration device; S3: drying and heat treating the composite solid electrolyte film precursor described in S2 to obtain a flexible composite solid electrolyte film; The vacuum filtration device and the porous base membrane containing inorganic solid electrolyte are both in operation, the speed difference between the two is 0.3-2.5 m / min, the filtration pressure between the porous base membrane containing inorganic solid electrolyte and the vacuum filtration device is 0.01-1 MPa; the pore coverage rate per unit area of the vacuum filtration device is 70-95%, and the pore area ranges from 0.01-10 mm 2 .
2. The method for preparing a continuously producible flexible composite solid electrolyte film according to claim 1; characterized in that: The particle size of the inorganic solid electrolyte is 1-500 nanometers; the solid content of the mixed solution A is in the range of 1-50wt%; the pore size of the porous base membrane in S1 is selected from 1-500 nanometers; Furthermore, the particle size of the inorganic solid electrolyte is preferably 50-200 nanometers; the pore size of the porous base membrane in S1 is preferably 250-400 nanometers.
3. The method for preparing a continuously producible flexible composite solid electrolyte film according to claim 1; characterized in that: The inorganic solid electrolyte is selected from one or more of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a nitride solid electrolyte, a phosphate solid electrolyte, and a borate solid electrolyte; wherein the oxide solid electrolyte includes one or more of a garnet solid electrolyte, a perovskite solid electrolyte, or a NASICON solid electrolyte; the garnet solid electrolyte includes lithium lanthanum zirconium oxide (LLZO) or a solid electrolyte obtained by replacing or doping LLZO with elements; the perovskite solid electrolyte includes lithium lanthanum titanium oxide (LLTO) or a solid electrolyte obtained by replacing or doping LLTO with elements; or modified solid electrolytes; NASICON solid electrolytes include lithium aluminum titanium phosphate (LATP) and lithium aluminum germanium phosphate (LAGP) or solid electrolytes obtained by replacing, doping or modifying LATP or LAGP with elements; sulfide solid electrolytes include LGPS or solid electrolytes obtained by replacing, doping or modifying LGPS with elements; halide solid electrolytes include Li2MnCl4 and Li2ZnCl4; nitride solid electrolytes include lithium nitride Li3N; phosphate solid electrolytes include lithium phosphate Li3PO4; borate solid electrolytes include LiBO2 and Li4B2O5; The type of the porous base membrane in S1 is selected from a polymer-based porous base membrane or a natural polymer-based porous base membrane; wherein the polymer-based porous base membrane includes one or more of polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polyurethane (PU), polyacrylonitrile (PAN), polyethylene oxide (PEO), polystyrene (PS), polyvinyl chloride (PVC), polycarbonate (PC), polymethyl methacrylate (PMMA), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), copolymer of vinylidene fluoride and hexafluoropropylene (PVDF-HFP), and polyimide (PI); the natural polymer-based porous base membrane is selected from cellulose membrane and its derivatives.
4. The method for preparing a continuously producible flexible composite solid electrolyte film according to claim 1; characterized in that: The mixed solution A in S1 includes a solvent; the type of the solvent is selected from one or more of water, ethanol, isopropanol, glycerol, ethylene glycol, tetrahydrofuran, N,N-dimethylformamide, and N-methylpyrrolidine; the drying temperature in S3 is selected from 60-100 degrees, and the drying time is selected from 6-24 hours; the heat treatment method in S3 is selected from one of hot pressing or roller pressing; the pressure range is 20-50kg / cm 2 , temperature is 50-130 degrees, time is 1-15min.
5. The method for preparing a continuously producible flexible composite solid electrolyte film according to claim 1; characterized in that: The vacuum filtration device in S2 is selected from a roller-shaped vacuum filtration device or a parallel box-type vacuum filtration device.
6. The method for preparing a continuously producible flexible composite solid electrolyte film according to claim 5; characterized in that: The roller-shaped vacuum filtration device comprises a vacuum filtration roller (1) for adsorbing a porous base film containing an inorganic solid electrolyte; a first rotating shaft (2) is provided inside the vacuum filtration roller (1) for driving the vacuum filtration roller to rotate; and a first suction hole (3) is also provided on the surface of the vacuum filtration roller (1); Furthermore, the roller-shaped vacuum filtration device also includes a flexible covering film (4); the flexible covering film (4) is adsorbed on the surface of the vacuum filtration roller (1) through a second rotating shaft (9); and is used to cover the portion of the vacuum filtration roller (1) that is not in contact with the porous base film containing the inorganic solid electrolyte.
7. The method for preparing a continuously producible flexible composite solid electrolyte film according to claim 5; characterized in that: The parallel box type vacuum filtration device comprises a vacuum filtration box (5) for adsorbing a porous base membrane containing an inorganic solid electrolyte; the surface of the vacuum filtration box (5) is provided with a second suction hole (6); and both sides of the vacuum filtration box (5) are respectively provided with a third rotating shaft (7) for driving the porous base membrane containing an inorganic solid electrolyte to move.
8. The method for preparing a flexible composite solid electrolyte film that can be produced continuously according to claim 1; characterized in that: The running speed of the vacuum filtration device is selected from 0.1-10 m / min, and the speed difference with the porous base membrane containing inorganic solid electrolyte is preferably 0.5-2 m / min. The pore coverage per unit area of the vacuum filtration device is preferably 75-90%, and the range of pore area is preferably 0.1-10 mm 2 .
9. A continuously producible flexible composite solid electrolyte film obtained by the preparation method according to any one of claims 1 to 8; characterized in that: The film has a thickness of 10-40 μm and a tensile strength of 10-80 MPa.
10. A battery or energy storage device, characterized in that: The battery or energy storage device comprises the flexible composite solid electrolyte film according to claim 9.
Citation Information
Patent Citations
Flexible inorganic solid-state electrolyte thin film and preparation and application thereof
CN108808075A
Covalent organic framework-based semi-solid electrolyte composite diaphragm as well as preparation method and application thereof
CN115312966A
Conductive composition for solar cell bonding, cured product thereof, and solar cell module manufactured using the same
KR1020200101196A
Modified solid electrolyte membrane and preparation method therefor, and lithium battery
WO2020087873A1
Cited By
Low-impedance electrolyte film for flexible solid-state battery and preparation method of low-impedance electrolyte film
CN122202485A